Co-modulation of finely tuned high-gamma band activity across hemispheres in Parkinson’s disease - Cagnan, H; Kuhn, A; Brown, P (Elsevier, 2013)
Objective: Dopaminergic treatment of patients with Parkinson’s disease can be associated with a finely tuned high-gamma (FTG) band oscillation between 60 and 90 Hz in the basal ganglia (BG) nuclei. This activity, together with suppression of excessive neural synchrony in the beta frequency band (15–30 Hz), is hypothesized to contribute to the pro-kinetic effects of dopaminergic medication. Beta activity, which high-gamma replaces, has been shown to be bilaterally coherent, but whether sub-cortical FTG activity is in some way linked across hemispheres remains unknown. Methods: We analyse bilateral local field potential activity recorded from the subthalamic nuclei of 10 patients on dopaminergic medication while at rest, following surgery for deep brain stimulation. Results: In three of these patients FTG activities were coherent across the hemispheres. Short duration (⩽18 s) bilateral amplitude and frequency co-modulation were recorded in all subjects, although the two phenomena were independent in time and independent of similar episodes in other frequency bands. Conclusions: FTG co-modulation can be independent of movement and of co-modulation episodes at other frequencies. Significance: Relatively independent organisation of processing through amplitude and frequency modulation within different frequency bands potentially affords opportunities for functional segregation and multiplexing of processing streams within the BG.